Terahertz-optical intensity grating for creating high-charge, attosecond electron bunches. (28th March 2019) - Lim, Jeremy; Chong, Yidong; Wong, Liang Jie
Abstract: Ultrashort electron bunches are useful for applications like ultrafast imaging, coherent radiation production, and the design of compact electron accelerators. Currently, however, the shortest achievable bunches, at attosecond time scales, have only been realized in the single- or very few-electron regimes, limited by Coulomb repulsion and electron energy spread. Using ab initio simulations and complementary theoretical analysis, we show that highly-charged bunches are achievable by subjecting relativistic (few MeV-scale) electrons to a superposition of terahertz and optical pulses. We provide two detailed examples that use realistic electron bunches and laser pulse parameters which are within the reach of current compact set-ups: one with bunches of >240 electrons contained within 20 as durations and 15 μ m radii, and one with final electron bunches of 1 fC contained within sub-400 as durations and 8 μ m radii. Our results reveal a route to achieve such extreme combinations of high charge and attosecond pulse durations with existing technology.